A Survey of Race Relations in South Africa 1972 (Berkeley : University of California Press, 2022)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1973.
URBAN ADMINISTRATION -- THE PASS LAWS -- THE AFRICAN HOMELANDS -- GENERAL MATTERS -- EMPLOYMENT -- EDUCATION -- BANTU SCHOOL EDUCATION -- STANDARDS OF EDUCATION ACHIEVED BY THE WHITE, COLOURED, AND ASIAN PEOPLE OF THE REPUBLIC -- SCHOOL EDUCATION FOR MEMBERS OF THE COLOURED COMMUNITY -- SCHOOL EDUCATION FOR INDIANS -- EDUCATION FOR CHINESE AND JAPANESE CHILDREN -- SCHOOL EDUCATION FOR WHITE CHILDREN -- TECHNICAL AND VOCATIONAL TRAINING -- UNIVERSITY EDUCATION -- UNIVERSITY EDUCATION -- SCHOLARSHIPS -- HEALTH -- WELFARE -- SPORT -- RECREATION -- SOUTH WEST AFRICA (NAMIBIA) -- INDEX
Description based upon print version of record.
JSTOR
Keywords: South Africa -- Race relations; South Africa -- Social conditions -- 1961-1994.; Afrique du Sud -- Relations raciales; Afrique du Sud -- Conditions sociales -- 1961-1994.; Race relations; Social conditions; South Africa; 1961-1994